Imidazole-linked crystalline two-dimensional polymer with ultrahigh proton-conductivity - Ranjeesh, Kayaramkodath Chandran; Ilathvalappil, Rajith; Veer, Sairam Dnyaneshwar; Peter, Joseph; Wakchaure, Vivek Chandrakant; Goudappagouda; Raj, K. Vipin; Kurungot, Sreekumar; Babu, Sukumaran Santhosh (Journal of the American Chemical Society, 2019)
Proton-exchange membrane fuel cells are promising energy devices for a sustainable future due to green features, high power density, and mild operating conditions. A facile proton-conducting membrane plays a pivotal role to boost the efficiency of fuel cells, and hence focused research in this area is highly desirable. Major issues associated with the successful example of Nafion resulted in the search for alternate proton conducting materials. Even though proton carrier loaded crystalline porous organic frameworks have been used for protonconduction, the weak host-guest interactions limited their practical use. Herein, we developed a crystalline 2D-polymer composed of benzimidazole units as the integral part, prepared by the condensation of aryl acid and diamine in polyphosphoric acid medium. The imidazole linked-2D-polymer exhibits ultrahigh proton conductivity (3.2 X 10(-2) S cm(-1)) (at 95% relative humidity and 95 degrees C) in the pristine state, which is highest among the undoped porous organic frameworks so far reported. The present strategy of a crystalline proton-conducting 2D-polymer will lead to the development of new high performing crystalline solid proton conductor.